Književnost očima Druge –Što... ili tko je monstrum kis Tatjane Tolstoj? - Maja Pandžić ([sic], 2019)
This article deals with the concept/identity of the monster kys in Tatyana Tolstaya’s novel of the same title (Kys, 2000). By drawing on the theory of feminist literary critics Sandra Gilbert and Susan Gubar, this work interprets kys as the articulation of the author’s resistance to patriarchal politics in Russian literature. In creating the post-apocalyptic society, Tolstaya depicts traditional gender roles, chooses a male protagonist and inserts numerous citations from literary works written exclusively by male authors. Nevertheless, even though in such a manner she appears to be imitating the dominant (male) literary tradition and depriving female characters of their voice, other elements lead to a different conclusion. For instance, the images of patriarchal society are primarily carnivalesque, while the classical notion of “the angel in the house” undergoes demythologization. Kys itself is gradually taking over the protagonist’s mind transforming him into her own embodiment – a monster which in her passionate yearning for books will stop at nothing – and so creates her own story in the process.